The Importance of Ergonomic Work Station Presence at Home during Covid-19 Quarantine in Indonesia - Fandita Tonyka Maharani; Dyah Utari; Farahdina Bachtiar; Condrowati Condrowati; Yuridista Putri Pratiwi (Perhimpunan Ergonomi Indonesia, 2021)
Background: Covid-19, which was declared by the WHO as a global pandemic on March 11, 2020, quickly change our way of life. Working from home becomes our new way of work to limit the virus spread. This study aims to present the musculoskeletal complaints by the workers and students, understand the related factors, and propose the ergonomic work station design to reduce the complaints. Methods: We spread the standardized Nordic Questionnaire through google form randomly. The 104 participants living in Indonesia participate in this study. We interview them about the work station they used at home. The questions about the perception of a “good” working position also asked. The logistic regression risk factor model was used to understand the significance of variables. Results: 42 % of respondents do not use chairs and only sit on the floor when working at home. 39.4 % of respondents work 4-6 hours/day. 67.3 % of respondents have musculoskeletal complaints, mostly felt in the neck (54 %). There was no association between the variables. Conclusion: We strongly argue that the ergonomic work station must be implemented at home during the Covid-19 quarantine in Indonesia.